Association of monetary diet cost of foods and diet quality in Spanish older adults - Bouzas, Cristina; Pastor, Rosario; García, Silvia; Monserrat-Mesquida, Margalida; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Schröder, Helmut; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; et al. (Frontiers in Public Health, 2023)
Background A major barrier to a healthy diet may be the higher price of healthy foods compared to low-quality foods. Objectives This study aimed to assess the association between the monetary cost of food and diet quality in Spanish older adults at high risk of cardiovascular disease. Methods Cross-sectional analysis was carried out in Spanish older adults (n = 6,838; 48.6% female). A validated food frequency questionnaire was used to assess dietary intake. Metabolic syndrome severity, adherence to the Mediterranean diet (MedDiet), adherence to a provegetarian dietary pattern, and dietary inflammatory index were assessed. The economic cost of the foods was obtained from the Spanish Ministry of Agriculture Fisheries and Food database (2015–2017, the period of time when the participants were recruited). The total cost of diet adjusted per 1,000 kcal was computed. Results The healthier dietary pattern was associated with a higher cost of the diet. Higher adherence to the MedDiet, anti-inflammatory diet, and the healthy version of the provegetarian dietary pattern were related to higher costs of the diet. Conclusion Higher diet quality was associated with a higher dietary cost of the diet per 1,000 kcal/day. Food prices can be an important component of interventions and policies aimed at improving people's diets and preventing diet-related chronic diseases. Clinical trial registry number The trial was registered in 2014 at the International Standard Randomized Controlled Trial (ISRCT; http://www.isrctn.com/ISRCTN89898870) with the number 89898870.